2011
DOI: 10.1097/mnh.0b013e32834b8850
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C as a marker of glomerular filtration rate

Abstract: Cystatin C may have a role to estimate GFR in selected circumstances, and the next set of studies should be directed at developing implementation strategies for its use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 61 publications
0
42
0
1
Order By: Relevance
“…31 Additionally, it has been shown to be affected by demographic factors, diabetes status, white blood cell count, albumin and C-reactive protein levels independent of GFR. 32 Yet, in the general population, cystatin C has been shown to correlate with mGFR more strongly than creatinine. 33,34 Furthermore, eGFR calculated using cystatin C has been shown to have stronger associations with cardiovascular disease, all-cause mortality, and ESRD when compared with eGFR calculated using creatinine.…”
Section: Cystatin C Based Estimates Of Gfrmentioning
confidence: 99%
“…31 Additionally, it has been shown to be affected by demographic factors, diabetes status, white blood cell count, albumin and C-reactive protein levels independent of GFR. 32 Yet, in the general population, cystatin C has been shown to correlate with mGFR more strongly than creatinine. 33,34 Furthermore, eGFR calculated using cystatin C has been shown to have stronger associations with cardiovascular disease, all-cause mortality, and ESRD when compared with eGFR calculated using creatinine.…”
Section: Cystatin C Based Estimates Of Gfrmentioning
confidence: 99%
“…Epidemiological studies have found that eGFR measurements based on cystatin C (eGFRcys) show a stronger association with renal and CVD outcomes than GFR estimated according to the creatinine level (eGFRcre) [1,2]. Because there is little evidence indicating that cystatin C is more effective for estimating GFR compared to creatinine, this superior risk prediction by eGFRcys may be caused by the confounding of non-GFR determinants of cystatin C and creatinine [3,4]. Several studies have shown eGFR to be influenced by traditional CVD risk factors independently of the measured GFR (mGFR).…”
Section: Introductionmentioning
confidence: 99%
“…However, until recently, the lack of a common standard resulted in large differences among assays [10,[54][55][56].…”
Section: Cystatin C Assaysmentioning
confidence: 99%
“…Their use is recommended in nephrology [1] and radiology guidelines [2][3][4][5], and in contrast medium textbooks [6] to identify patients at risk of CIAKI or nephrogenic systemic fibrosis [7]. The last decade has seen an increased interest in cystatin C to supplement creatinine in new equations to estimate GFR [8][9][10]. Unfortunately, issues of calibration of creatinine and cystatin C assays with regard to selection of GFR equation are generally not discussed in CIAKI studies or given enough consideration in guidelines or textbooks.…”
Section: Introductionmentioning
confidence: 99%